Electrochemical analysis of carbon nanotubes/titanium dioxide composite modified glassy carbon electrode - Perenlei, Ganchimeg (2010)
The new chemically modified electrode based on carbon nanotubes/titanium dioxide (CNT/Ti02) composite modified glassy carbon electrode (GCE) was fabricated by two different (i) mechanical attachment and (ii) solvent casting methods. The CNT/Ti02/GCE composite has been characterized using voltammetric techniques of linear sweep voltammetry, cyclic voltammetry, chronoamperometry and chronocoulometry in this work. The surface morphology of the CNT/Ti02 composite film was studied by scanning electron microscopy and the percentage of the elements in components was examined by energy dispersive X-ray. The CNT/Ti02/CGE was applied in the electrochemical determination of 0.5 mM ascorbic acid in 0.1 M NaCI (pH 6.2), 0.1 mM potassium ferricyanidc in 0.1 M Na2HP04 (pH 8.5) and 0.2 mM paracetamol in 0.1 M PBS (pH 7.0). The current enhancements of 5.0 folds for the oxidation of ascorbic acid, 3.0-3.1 folds for the redox of potassium ferricyanide and 8.5-11.0 folds for the redox of paracetamol were obtained using the CNT/Ti02/GCE when compared with unmodified GCE. The responses of each analyte at various electrodes are in the order: CNT/Ti02/GCE > CNT/GCE > GCE > Ti02/GCE Under the optimized parameters, the linear calibration graph showed correlation coefficient of 0.997 for the oxidation of 0.05-2 mM ascorbic acid, 0.999 for the redox of 0.01-0.2 mM potassium ferricyanide and the concentration isotherm of paracetamol in the range of 0.0 I - 2 mM, with linearity of up to 1.2 mM. From this calibration plot, high sensitivity response of 45 JlA/mM with detection limit of 7.8 JlM (100 mVIs scan rate) for the oxidation of ascorbic acid; 68.9-77.6 JlA/mM with 1.1 ~tM (5 mVis) for the redox of potassium ferricyanide; and 89.94-111.3 JlA/mM with 3.9 uM (5 mV/s) for the redox of paracetamol at the CNT/Ti02/GCE were obtained. Effect of scan rate of ascorbic acid was studied in the ranges of 10-300 mVis, and linear relation was observed up to 70 mVis. Based on the log plot of oxidation current vs. scan rate, an experimental slope of 0.45 was obtained, which is very close to the theoretical value of 0.5, indicating that the current is under diffusion controlled. Based on redox currents of potassium ferricyanide vs. potential plot, the zero-current potentials were obtained at Ega=209 mV and Egc= 189 mV in the scan rates ranges of 10-600 mVIs. Diffusion coefficient was calculated as 1.52x 10.5 cm2/s from the chronocoulometry study and an activation energy obtained was 6 kl/mol in the presence of potassium ferricyanide in aqueous media at the composite electrode. The redox peak currents of paracetamol were significantly dependent on dosages of CNT to Ti02 in the composite at GCE. The recovery experiment of paracetamol in commercially available samples was carried out and the recovery rates of 95±2% and 96±2% were found using the CNT/Ti02/GCE. The results revealed that the electrochemical ability of CNT is improved when combined with Ti02 nanoparticles as a composite. The use of the CNTITi02/GCE IS highly sensitive, selective and stable in electrochemical measurement.